Facts and myths about use of esketamine for treatment-resistant depression: a narrative clinical review - Di Vincenzo, Matteo; Martiadis, Vassilis; Della Rocca, Bianca; Arsenio, Eleonora; D’Arpa, Andrea; Volpicelli, Antonio; Luciano, Mario; Sampogna, Gaia; Fiorillo, Andrea (Frontiers in Psychiatry, 2024)
Introduction and aims Treatment-resistant depression (TRD) occurs when at least two different antidepressants, taken at the right dosage, for adequate period of time and with continuity, fail to give positive clinical effects. Esketamine, the S-enantiomer of ketamine, was recently approved for TRD treatment from U.S. Food and Drug Administration and European Medicine Agency. Despite proved clinical efficacy, many misconceptions by clinicians and patients accompany this medication. We aimed to review the most common “false myths” regarding TRD and esketemine, counterarguing with evidence-based facts. Methods The keywords “esketamine”, “treatment resistance depression”, “depression”, “myth”, “mythology”, “pharmacological treatment”, and “misunderstanding” were entered in the main databases and combined through Boolean operators. Results Misconceptions regarding the TRD prevalence, clinical features and predictors have been found. With respect of esketamine, criteria to start treatment, dissociative symptoms, potential addiction and aspects of administration and monitoring, were found to be affected by false beliefs by clinicians and patients. Discussion and conclusion TRD represents a challenging condition, requiring precise diagnosis in order to achieve patient’s full recovery. Esketamine has been proved as an effective medication to treat TRD, although it requires precautions. Evidence can inform clinical practice, in order to offer this innovative treatment to all patients with TRD.